Positional Stability and Membrane Occupancy Define Skin Fibroblast Homeostasis In Vivo - Marsh, Edward; Gonzalez, David G.; Lathrop, Elizabeth A.; Boucher, Jonathan; Greco, Valentina (Cell, 2018)
Fibroblasts are an essential cellular and structural component of our organs. Despite several advances, the critical behaviors that fibroblasts utilize to maintain their homeostasis in vivo have remained unclear. Here, by tracking the same skin fibroblasts in live mice, we show that fibroblast position is stable over time and that this stability is maintained despite the loss of neighboring fibroblasts. In contrast, fibroblast membranes are dynamic during homeostasis and extend to fill the space of lost neighboring fibroblasts in a Rac1-dependent manner. Positional stability is sustained during aging despite a progressive accumulation of gaps in fibroblast nuclei organization, while membrane occupancy continues to be maintained. This work defines positional stability and cell occupancy as key principles of skin fibroblast homeostasis in vivo, throughout the lifespan of mice, and identifies membrane extension in the absence of migration as the core cellular mechanism to carry out these principles. [Display omitted] •Skin fibroblasts are positionally stable in non-remodeling tissue after cell loss•Fibroblasts extend their membrane into depleted areas in a Rac1-dependent manner•Membrane extension is incorporated with known repair behaviors in larger damage•Aging fibroblasts are lost in stable clusters, compensated by a neighboring membrane Skin fibroblasts maintain their position over time, but upon injury or during aging, they can extend spatially to compensate for neighboring cell loss as a homeostatic mechanism.